2010
DOI: 10.1016/j.ultrasmedbio.2010.08.023
|View full text |Cite
|
Sign up to set email alerts
|

A Tissue Phantom for Visualization and Measurement of Ultrasound-Induced Cavitation Damage

Abstract: Many ultrasound studies involve the use of tissue-mimicking materials to research phenomena invitro and predict in-vivo bioeffects. We have developed a tissue phantom to study cavitationinduced damage to tissue. The phantom consists of red blood cells suspended in an agarose hydrogel. The acoustic and mechanical properties of the gel phantom were found to be similar to soft tissue properties. The phantom's response to cavitation was evaluated using histotripsy. Histotripsy causes breakdown of tissue structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 43 publications
5
132
0
Order By: Relevance
“…Agarose gel phantoms with an embedded red blood cell (RBCs) layer were used to demonstrate the ability of using nanodroplets to mechanically ablate tissue. 44 This phantom provides a thin, translucent red layer of RBCs as a visual indicator between the two transparent agorose gel layers that locally appears more transparent when RBCs layer is damaged. Tissue phantoms were prepared using a mixture of agarose powder (type VII; Sigma-Aldrich Co., St. Louis, Missouri, USA) and canine RBCs in 0.9% isotonic saline.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Agarose gel phantoms with an embedded red blood cell (RBCs) layer were used to demonstrate the ability of using nanodroplets to mechanically ablate tissue. 44 This phantom provides a thin, translucent red layer of RBCs as a visual indicator between the two transparent agorose gel layers that locally appears more transparent when RBCs layer is damaged. Tissue phantoms were prepared using a mixture of agarose powder (type VII; Sigma-Aldrich Co., St. Louis, Missouri, USA) and canine RBCs in 0.9% isotonic saline.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…27 However, in vitro studies of histotripsy utilize phantoms of highly degassed agar to monitor bubble dynamics. 6,28,29 As noted in Fig. 4(A), the equilibrium diameter, and therefore the duration of bubble persistence, is reduced in degassed media compared to physiologic gas saturated media.…”
Section: Representative Calculationmentioning
confidence: 72%
“…Maxwell et al 3 demonstrated that HIFU-induced cavitation can be visualized using agarose hydrogel TM phantom supplemented with red blood cells (RBCs). In their study, RBC-agarose TM phantom was prepared by solidifying agarose phantom, pouring RBCs onto the agarose phantom, allowing it to solidify again, and finally, pouring agarose solution onto the RBCs-suspended agarose phantom.…”
Section: Periscopementioning
confidence: 99%
“…In their study, RBC-agarose TM phantom was prepared by solidifying agarose phantom, pouring RBCs onto the agarose phantom, allowing it to solidify again, and finally, pouring agarose solution onto the RBCs-suspended agarose phantom. 3 Additionally, in order to simulate interactions between laser energy and hair shafts, our study group also developed a hair shaft-embedded bovine serum al-A B bumin and polyacrylamide hydrogel-based TM phantom. To do so, TM phantom was prepared by mixing polyacrylamide hydrogel and 5% (w/v) bovine serum albumin in distilled water.…”
Section: Periscopementioning
confidence: 99%